ANAK, MINAT BACA, DAN MENDONGENG - I Ketut Artana (ACARYA PUSTAKA, 2017)
Children's reading interest today is not encouraging. Various facts and data on statistical reports related to reading interest and reading ability among children show that children's reading interest is still low. The role of parents or family or other parties are required to do or make a way of strategy for the interest of reading children can grow and develop well. One effort to foster interest in reading in children is to tell stories. Basically fairy tales contain positive values for life, because in it contained moral and ethical demands. Storytelling is one effort or technique to foster reading interest in children. Parents or other family members as well as other parties can act as speakers of the books they read and, of course, fairytale material adapted to the level of language development and age of the child. The storytelling activity will be more effective when delivered or told at bedtime, during the family relax time, or it can be given ahead of and after class lesson. If the activity is done well, continuously, will gradually arise the child's desire to read their own books. Therefore storytelling is one of the best ways to foster reading interest in children. Keywords: reading interest, storytelling, children